Peningkatan Self Awareness Anak Usia Dini Melalui Media Video Mitigasi Bencana Gunung Meletus - Ningtyas, Dhita Paranita; Risina, Duana Fera (PROGRAM STUDI PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD), FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2018)
This study aims to improve children's self-awareness in disaster response, especially volcanic eruptions with result that children are able to understand the danger of volcanic eruptions since early and have an awareness through a disaster. The subjects were children in group B TK Pertiwi 1 and 2 Samiran, aged 5-6 years. The study was carried out in the village of Samiran because it was an area under the foot of Mount Merapi and Merbabu. This study uses